2017
DOI: 10.22543/7674.42.p186192
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic challenges in a case of psoriasis with nail onset

Abstract: Nail psoriasis affects a large number of patients with psoriasis and has a major psychosocial impact. Furthermore, it may be regarded as a predictor of more severe forms of psoriasis and early sign of psoriatic arthritis. The clinical presentations vary depending on the structure affected (nail matrix or nail bed), the nail lesions may range from minor to severe, but they are not specific. Treatment is a challenge, in most cases the lesions being resistant to therapy. We present a rare case of psoriasis with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…18,19 Psoriasis is proposed to be an autoimmune ailment caused by improper activation of the cellular IgGanti-IgA antibody levels, modification in function of polymorph nuclear leukocytes reduces the no of T cells, and a rise in activity of beta cells. 2…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Psoriasis is proposed to be an autoimmune ailment caused by improper activation of the cellular IgGanti-IgA antibody levels, modification in function of polymorph nuclear leukocytes reduces the no of T cells, and a rise in activity of beta cells. 2…”
Section: Resultsmentioning
confidence: 99%
“…1 The two peaks of onset of psoriasis are between the age 20 to 30 years and between the age of 50 to 60 Years and t equally in both sexes. 2 This ailment may be associated with various comorbidities including malignancy and cardiovascular problem. 3 The disease has poor impact on quality of life including impact on quality of life including the problems of anxiety, depression, stigma and in some cases suicidal deeds.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Mitran et al in 2017 in Romania reported that psoriasis vulgaris could occur at any age, with the highest incidence in the age group of 15-30 years, and it rarely occurs before the age of 10 years. 12 The genetic role of human leukocyte antigen (HLA) class I, especially HLA-Cw6, is associated with earlier age onset and a family history of the positive ones. 13 In this study, the PASI score was found to be higher for females with an average of 18.40, compared to males with an average of 15.76.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a chronic noncommunicable inflammatory skin disease affecting nearly 2% of the population with equal incidence in males and females [1] . This disease can affect any age, but its incidence is high in the 20s and 50s [2] . Due to its disfigurement effect, the patients often suffer from poor quality of life, depression and/or anxiety extending to the level of suicidal attempts [3,4] .…”
Section: Introductionmentioning
confidence: 99%